World book 2004 (Chicago World Book, 2003)
Searchable database of reference entries in the World Book encyclopedia. Includes thousands of articles as well as pictures, videos, and hundreds of detailed maps.
CD-ROM.
System requirements: MS Windows ME, 2000, 98, 95B, NT 4.0, XP; Pentium or higher IBM or 100% compatible PC, 16 MB RAM (32 MB recommended); 100 MB free hard disk space; 16-bit sound card; 16-bit color recommended; CD-ROM drive (2x speed or faster); mouse; Internet Explorer 4 or higher.
Keywords: Encyclopedias and dictionaries